المشكلات الاجتماعية وتأثيرها على النمو الاجتماعي والمعرفي للطفل - دراسة ميدانية على عينة من الأطفال العاملين - عزيز, سامية; كزيز, أمال (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الورقة البحثية إلى دراسة أحد مظاهر المشكلات الاجتماعية في المجتمع الجزائري وهي عمالة الأطفال، كونها تعد من الظواهر الجديرة بالبحث والدراسة والتي تعبر عن التحاق الطفل إلى عالم الشغل في سن صغير، ومن هنا تم التركيز على عينة من الأطفال العاملين بمدينة بسكرة، وتم الاعتماد على المنهج الكيفي وأداة المقابلة وتم التوصل إلى أن الطفل العامل يتأثر نموه المعرفي والاجتماعي كونه في وسط العمل. Abstract: This research paper aimed to study one of the aspects of social problems in Algerian society, which is child labor, as it is considered one of the phenomena worthy of research and study, which expresses the enrollment of the child to the world of work at a young age of no more than fifteen, and which leaves many effects on society in general and on The child, especially as it affects childhood, which is one of the most important stages of the child's development and the most influential in their lives and in their social, family and school upbringing, and from here the focus was on a sample of working children in Biskra, and the descriptive approach and the interview tool were relied upon and it was concluded that the working child is affected by his growth Cognitive and social being in the middle of work.
Social problems and their impact on the child's social and cognitive development - A field study on a sample of working children
مقال
Keywords: عمالة الأطفال، النمو المعرفي، التنشئة الاجتماعية، الطفولة، المجتمع; child labor, cognitive development, socialization, childhood, society.